Pemberdayaan Kelompok Pembudidaya Ikan (Pokdakan) Tempuling Madani Jaya dalam Domestikasi Ikan Betutu (Oxyeleotris marmorata) Sebagai Komoditas Budidaya Perikanan Berkelanjutan - Syaiful Ramadhan Harahap; Khairul Ihwan; Arief Rachman B; Toni Anggara; Muhammad Arif Aljumadi; Abdul Gani; Gusmanto Gusmanto; Muhammad Thaha (PELANTAR PRESS, 2025)
This community service program assesses the implementation of Betutu fish (Oxyeleotris marmorata) domestication in the Tempuling District, Indragiri Hilir Regency, as part of a community empowerment program aimed at enhancing local fish farming practices and promoting sustainable aquaculture. The program focused on introducing various technologies, including the use of tarpaulin ponds with a water recirculation system, fish feed formulated from local bycatch and EM4, and digital water quality monitoring. These innovations have successfully increased Betutu fish production by 20%. Additionally, the program introduced digital marketing strategies through social media and e-commerce platforms, resulting in a 20% increase in product sales. Beyond economic benefits, the program also enhanced the technical skills and entrepreneurial capacity of the local fish farming community, thereby strengthening their economic independence and improving social welfare. With efficient production capacity and effective marketing strategies in place, the program is poised for sustainability and offers a solution to the declining Betutu fish population. This initiative serves as a model for community-based technological empowerment that can be replicated in other regions, accelerating local economic development and ensuring long-term societal well-being